NILAI-NILAI DAKWAH DALAM LONTARA TARO ADA TARO GAU (STUDI KEPEMIMPINAN RUMAH TANGGA DI KABUPATEN BONE) - Syafriana Ana; Sattu Alang; Kamaluddin Tajibu (Fakultas Dakwah dan Komunikasi, 2020)
Basically Islam is very dominant form the behaviour of Bugis people in communicating because the value of Bugis culture has experienced the process of Islamization, namely when the entry of the element Sara' (Syari’at) colouring and become the spirit of the elements In Pangadereng so that the dance is no longer a stretch of religion with Islamic teachings. If a leader has a desire and determination to apply the Taro communication attitude There is taro gau, then realize in the leadership of his household, then it is an excellent effort in maintaining the house integrity His household. The Bugis people usually socialize in the family about the admonitions like this and will grow from individuals into families and will eventually become a unit of society implementing the Taro attitude their taro gau, Four Principal value in the Taro Taro Ada taro Gau, namely Macca or to acca (smart), Malempu (honest), Magetteng na Warani (strong and brave) and Manini(thorough).